Pengaruh Penilaian Kinerja Kinerja Dan Etos Kerja Terhadap Promosi Jabatan pada PT Midi Utama Indonesia Tbk - M Yusuf (Fakultas Ekonomi Dan Bisnis Universitas Tjut Nyak Dhien, 2024)
The aim of the research is to determine the effect of performance appraisal and work ethic changes on employee promotion. This research was carried out at PT Midi Utama Indonesia Tbk with a population and sample of 83 employees. This research instrument is a questionnaire with a Likert scale model. Requirements tests are carried out to test normality. The data analysis technique used is the Multiple Regression technique at a significance level of a = 0.05. The results of this research show that Performance Assessment (X1) has a significant and influential effect on PT Midi Utama Indonesia Tbk Employee Position Promotion with a significant value of 0.000. Meanwhile, Work Ethics (X2) has a significant influence on the Promotion of PT Midi Utama Indonesia Employee Positions with a significant value of 0.000.